Health coaching for individuals with type 2 diabetes: assessing the impact of health coaching on HbA1c, hospitalizations, and outpatient services - Gittens, Anthony; Medina, Ernie; Oh, Jisoo; Nelson, Anna; Aréchiga, Adam (Frontiers in Endocrinology, 2025)
IntroductionThe global prevalence of type 2 diabetes mellitus (T2DM) presents substantial public health challenges, particularly among Medicaid populations. Health coaching has emerged as a promising intervention to improve glycemic control and healthcare utilization.MethodsWe conducted a retrospective pre-post secondary data analysis of 4,583 CalOptima Medicaid recipients with T2DM between March 2015 and August 2023. Patients who received health coaching (n = 3,777) were compared to those who declined (n = 806). Primary outcomes included HbA1c, hospitalizations, and outpatient visits.ResultsThe coached group experienced a significantly greater reduction in HbA1c (MD = -1.14, SD = 1.98) compared to the non-coached group (MD = -0.80, SD = 1.96; t(4581) = 4.51, p < .001). Ambulatory visits increased significantly among coached participants (p < .001), though hospitalizations showed no significant changes. Logistic regression indicated coached individuals had higher, though not statistically significant, odds of achieving normal HbA1c levels (OR = 1.19, 95% CI: 0.96–1.46).DiscussionHealth coaching was associated with improved glycemic control and increased ambulatory care engagement among Medicaid patients with T2DM. These findings highlight the value of patient-centered interventions in chronic disease management within underserved populations.